Severe cold-water bleaching of a deep-water reef underscores future challenges for Mesophotic Coral Ecosystems - Alan D. Foreman; Nicolas N. Duprey; Matan Yuval; Marielle Dumestre; Jennifer N. Leichliter; Mark C. Rohr; Rose C.A. Dodwell; Guy A.S. Dodwell; Eric E.G. Clua; Tali Treibitz; Alfredo Martínez-García (Science of The Total Environment, 2024)

Releasing a dataset of 3D models of artificial reefs from the northern red-sea for 3D printing and virtual reality applications - Matan Yuval; Tali Treibitz (Remote Sensing Applications: Society and Environment, 2024)

VARista: a free web platform for streamlined whole-genome variant analysis across T2T, hg38, and hg19 - Noam Hadar; Vadim Dolgin; Katya Oustinov; Yuval Yogev; Tomer Poleg; Amit Safran; Ofek Freund; Nadav Agam; Matan M. Jean; Regina Proskorovski-Ohayon; Ohad Wormser; Max Drabkin; et al. (Human Genetics, 2024)

Assessment of storm impact on coral reef structural complexity - Matan Yuval; Naama Pearl; Dan Tchernov; Stephane Martinez; Yossi Loya; Avi Bar-Massada; Tali Treibitz (Science of The Total Environment, 2023)

Evaluating biodiversity for coral reef reformation and monitoring on complex 3D structures using environmental DNA (eDNA) metabarcoding - Natalie Levy; Noa Simon-Blecher; Shachaf Ben-Ezra; Matan Yuval; Tirza Doniger; Matthieu Leray; Sarit Karako-Lampert; Ezri Tarazi; Oren Levy (Science of The Total Environment, 2023)

Needs and Gaps in Optical Underwater Technologies and Methods for the Investigation of Marine Animal Forest 3D-Structural Complexity - Paolo Rossi; Massimo Ponti; Sara Righi; Cristina Castagnetti; Roberto Simonini; Francesco Mancini; Panagiotis Agrafiotis; Leonardo Bassani; Fabio Bruno; Carlo Cerrano; Paolo Cignoni; Massimiliano Corsini; et al. (Frontiers in Marine Science, 2021)
Marine animal forests are benthic communities dominated by sessile suspension feeders (such as sponges, corals, and bivalves) able to generate three-dimensional (3D) frameworks with high structural complexity. The biodiversity and functioning of marine animal forests are strictly related to their 3D complexity. The present paper aims at providing new perspectives in underwater optical surveys. Starting from the current gaps in data collection and analysis that critically limit the study and conservation of marine animal forests, we discuss the main technological and methodological needs for the investigation of their 3D structural complexity at different spatial and temporal scales. Despite recent technological advances, it seems that several issues in data acquisition and processing need to be solved, to properly map the different benthic habitats in which marine animal forests are present, their health status and to measure structural complexity. Proper precision and accuracy should be chosen and assured in relation to the biological and ecological processes investigated. Besides, standardized methods and protocols are strictly necessary to meet the FAIR (findability, accessibility, interoperability, and reusability) data principles for the stewardship of habitat mapping and biodiversity, biomass, and growth data.